Social medias gig-economy participation amongst contemporary Malaysia Muslim entrepreneurs - Abdul Rahman, Saiful Nujaimi; Kamaruddin, Rohaidah; Syed Zainudin, Sharifah Sofiah; Yasin, Megat Al Imran (Allied Academies, 2022)
The Industrial Revolution 4.0 has brought immense significant changes towards global media operations amongst Muslims. Malaysia’s Muslims are of no exception. Among others include the wide usage of smart phones, computers, and latest gadgets as tool for setting-up numerous platforms for venturing into gig-economy. Such developments had altered the public media dependency upon the previous conventional media–especially in relation to publicizing, promoting, and marketing personal business products. Thus to date, data had shown that Malaysia’s Muslim Entrepreneurs’ participation are escalating in encouraging numbers. This latest platform of entrepreneurial arena is somehow different from the traditional marketing strategies adopted before. Numerous new methods and approaches had been applied since the arrival of the 4.0 revolution. Save but a few Malaysia’s Muslim Entrepreneurs understood the needs and requirements of this latest marketing realm. Most simply indulge without prior preparations. For that reason, this paper is aimed at assessing significant observations on the issue in particular. It will first discuss on the Industrial Revolution 4.0, then moving towards the demands of Web 2.0 and Web 3.0–before seeking for understandings in the realm of social media gig-economy, and Malaysia’s Muslim entrepreneurial participations. Few legislations will be brought into discussion, such as Communications and Multimedia Act 1998 (Act 588), Competition Act 2010 (Act 712), and Competition Commission Act 2010 (Act 713). Without prejudice, this paper deserve its audience–to the very least, it will shed lights for a much wider future discussions on Malaysia’s Muslim Entrepreneurs involving social media for gig-economy. Quoting Charles Darwin, On the Origin of Species by Means of Natural Selection, 1859: “It is not the strongest of the species that survives, or the most intelligent. It is the one that is the most adaptable to change”. In this very essence of adaptiveness, the survivals of contemporary Malaysia’s Muslim Entrepreneurs require competent and sufficient understanding on this matter. Nevertheless, may this paper become a beacon of reference amongst Malaysia’s Muslim Entrepreneurs–by not allowing them to be buffeted on the tides of history due to deliberate ignorance upon understanding the needs and requirements of social media platforms in the future and beyond?